The Role of Arrestin Domain-Containing 3 in Regulating Endocytic Recycling and Extracellular Vesicle Sorting of Integrin β4 in Breast Cancer - Soung, Young Hwa (Cancers (Basel), 2018)
Despite the established role of integrin β4 (ITG β4) in breast cancer progression, the importance of endocytic recycling of ITG β4 and its regulatory mechanism are poorly understood. Here, we found that a sub-population of ITG β4 is sorted into early endosomes, recycled back to the plasma membrane, and secreted in the form of extracellular vesicles (EVs) upon EGF treatment in triple negative breast cancer (TNBC) cells. A metastasis suppressor, ARRDC3 (arrestin domain-containing 3) prevents EGF-driven endocytic recycling of ITG β4 by inducing NEDD4-dependent ubiquitination of ITG β4 and targeting endosomal ITG β4 into lysosomes. Endocytic recycling of ITG β4 is linked to sorting of ITG β4 into EVs (ITG β4+ EVs). ITG β4+ EVs are mainly detectable from supernatants of TNBC cells and their production is inhibited by ARRDC3 expression. ARRDC3 reduces the metastatic potentials of breast cancer cell-derived EVs by reducing ITG β4 levels in EVs. Overall, current studies provide novel mechanistic insights on the regulatory mechanism of ITG β4 recycling, and its importance in invasive potentials of TNBC EVs, thus providing the basis for therapeutic targeting of the ARRDC3/ITG β4 pathway in TNBC.